Bile acids and gut microbiota: interactions and impacts on polycystic ovary syndrome - Qian, Haiqing; Tao, Jialing; Shi, Lingli; Sun, Haiyan; Yang, Li; Cui, Li juan; Xu, Wenting; Wang, Lihong (Frontiers in Microbiomes, 2026)
Polycystic ovary syndrome (PCOS) is a multifaceted endocrine and metabolic disorder intricately associated with hyperandrogenism (HA), insulin resistance (IR), chronic inflammation, and obesity. The gut microbiota (GM) is considered a mature endocrine organ capable of exerting multiple effects by regulating bile acids (BAs) metabolism. Disruption of GM homeostasis can initiate various pathological processes, including metabolic disorders, endocrine imbalances, low-grade inflammation, and reduced insulin sensitivity, thereby providing novel avenues for research into the pathogenesis of PCOS. There is bidirectional signalling between the GM and BAs: the microbial community tightly regulates the metabolism and synthesis of BAs, while the BAs pool and its composition affect the diversity and homeostasis of intestinal microorganisms. Dysregulation of BAs metabolism mediated by the GM may constitute a crucial pathological link in the progression of PCOS. The objective of this review is to investigate the function of BAs as a signalling molecule bridging the GM and PCOS, to synthesise the current understanding of the roles of BAs and intestinal microorganisms in the pathogenesis of PCOS, and to explore new treatment strategies for PCOS further.